Mineral and Geochemical Features of the Zengibobo-Sheikhjelinskaya Ore Bodies of the Dzhelinsky Area of the Sultanuizdag Ridge - Khodjaeva, Mukaddaskhon Khabibkhon kizi (RA Journal of Applied Research, 2022)
The mineralized zones of the Zengibobo-Sheikhjelinskaya area are timed to narrow violations of the tectonic zones of the north-eastern and north-western direction. The main form of gold-containing mineralization are small sharp-falling veins and lenses of quartz containing interspersed pyrite, arsenopyrite, chalcopyrite and pyrrotin, which are represented by gold-quartz, gold-arsenopyrite-pyrite natural type of ores.